Identification, Cloning, and Functional Characterization of Carotenoid Cleavage Dioxygenase (CCD) from Olea europaea and Ipomoea nil - Kaixuan Ke; Yufeng Zhang; Xinyi Wang; Zhaoyan Luo; Yangyang Chen; Xianying Fang; Linguo Zhao (Biology)
The aromatic C13 apocarotenoid β-ionone is a high-value natural-flavor and -fragrance compound derived from the oxidative cleavage of carotenoids. Carotenoid cleavage dioxygenases (CCDs) play a pivotal role in the biosynthesis of volatile apocarotenoids, particularly β-ionone. In this study, we report the identification, cloning, and functional characterization of two CCD1 homologs: OeCCD1 from Olea europaea and InCCD1 from Ipomoea nil. These two species, which, respectively, represent a woody perennial and a herbaceous annual, were selected to explore the potential functional divergence of CCD1 enzymes across different plant growth forms. These CCD1 genes were synthesized using codon optimization for Escherichia coli expression, followed by heterologous expression and purification using a GST-fusion system. In vitro assays confirmed that both enzymes cleave β-carotene at the 9,10 (9′,10′) double bond to yield β-ionone, but only OeCCD1 exhibits detectable activity on zeaxanthin; InCCD1 shows no in vitro cleavage of zeaxanthin. Kinetic characterization using β-apo-8′-carotenal as substrate revealed, for OeCCD1, a Km of 0.82 mM, Vmax of 2.30 U/mg (kcat = 3.35 s−1), and kcat/Km of 4.09 mM−1·s−1, whereas InCCD1 displayed Km = 0.69 mM, Vmax = 1.22 U/mg (kcat = 1.82 s−1), and kcat/Km = 2.64 mM−1·s−1. The optimization of expression parameters, as well as the systematic evaluation of temperature, pH, solvent, and metal ion effects, provided further insights into the stability and functional diversity within the plant CCD1 family. Overall, these findings offer promising enzymatic tools for the sustainable production of β-ionone and related apocarotenoids in engineered microbial cell factories.